Application value of contrast‐enhanced ultrasound in preoperative localization of microwave ablation for primary hyperparathyroidism. Issue 12 (17th October 2022) - Liu, Fangyi; Zang, Li; Li, Yunlin; Guan, Zhiwei; Liu, Yang; Yu, Xiaoling; Han, Zhiyu; Liang, Ping
Abstract: Background: Ultrasonography (US) and 99m Technetium‐sestamibi scintigraphy ( 99m Tc‐MIBI) are currently first‐line imaging modalities to localize parathyroid adenomas with sensitivities of 80% and 84%, respectively. Therefore, finding other modalities to further improve the diagnostic accuracy for preoperative localization is critically needed. Purpose: To evaluate the application value of contrast‐enhanced ultrasound (CEUS) in the preoperative localization of microwave ablation (MWA) for primary hyperparathyroidism (PHPT). Methods: Between December 2012 and May 2021, 100 PHPT patients (34 males and 66 females; mean age, 56.31 ± 13.43 years; age range, 25–85 years) with 130 suspected parathyroid nodules were enrolled. US, CEUS, and 99m Tc‐MIBI were performed for the localization of pathological parathyroid glands. All patients were performed MWA under ultrasound guidance. All the suspected parathyroid nodules underwent core needle biopsy under ultrasound guidance during MWA to confirm the pathology. The diagnostic performance of all the imaging tests was analyzed in comparison with the pathological results. Results: A total of 130 nodules suspected to be of parathyroid origin from preoperative localization images were confirmed by pathological results, of which 116 were of parathyroid origin, and 14 were not of parathyroid origin. The sensitivity, specificity, accuracy, and the area under receiver operating characteristic curve of CEUS in the localization of pathological parathyroid glands were 100%, 92.86%, 99.23%, and 0.964, which were significantly higher than those of US (93.10%, 42.86%, 87.69%, and 0.680) and 99m Tc‐MIBI (81.90%, 42.86%, 77.69%, and 0.624) ( p  < 0.05). The sensitivity and accuracy of CEUS were 100% and 97.22%, which were higher than those of 99m Tc‐MIBI (65.62% and 63.89%) or US (75.00% and 72.22%) in patients with multiple parathyroid glands ( p  < 0.05). For smaller parathyroid adenomas (≤2 cm in diameter), the sensitivities of CEUS in locating hyperfunctioning parathyroid glands were 100%, which was significantly higher than that of 99m Tc‐MIBI (73.68% and 84.31%, p  < 0.05). Conclusions: CEUS is a valuable preoperative localization method for PHPT patients performed MWA, especially for the patients with smaller pathological parathyroid gland and multiple glandular lesions.